The effect of task role on Vietnamese EFL learners' collaboration in mixed proficiency dyads. (April 2017) - Dao, Phung; McDonough, Kim
Abstract: Previous peer interaction research has shown that proficiency not only plays a role in how second language (L2) learners talk about language form, but also influences their pair dynamics. The current study focuses on peer interaction involving mixed-proficiency dyads, specifically whether task role affects the nature of L2 learners' discussions or their pair dynamics. Sixty English L2 learners at a Vietnamese university were assigned to mixed-proficiency dyads to carry out a story retell task. Task role was manipulated by assigning either information holder or information receiver status to the lower-proficiency learner. After retelling the story, the learners worked together to create a story ending and then collaboratively wrote the entire story. Audio-recordings of their interactions were transcribed and analyzed in terms of the amount, type, and resolution of language-related episodes (LREs) and pair dynamics. The results indicated that the learners produced more LREs and engaged in interactions with greater mutuality when the lower-proficiency learner had the task role as information holder. The findings shed light on ways to promote attention to language form and collaborative interactions when L2 learners from different proficiency levels carry out communicative tasks.